Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.